ECMO and impella increase stroke risk in acute myocardial infarction - Wu, Jing; Li, Chenguang; Xu, Zheng; Wang, Baoguo; Zhang, Mingyou (Scientific reports, 2025)
There is limited data on the risk of stroke in patients with acute myocardial infarction (AMI) treated with temporary mechanical circulatory support devices. Retrospective data were extracted from the U.S. National Inpatient Sample between October 2015 and December 2020, involving hospitalizations for AMI . The final cohort comprised: 4,370,069 hospitalizations with medical therapy only, 136,005 with intra-aortic balloon pump (IABP) only, 41,560 with Impella only, and 10,695 with extracorporeal membrane oxygenation (ECMO) utilized during hospitalization. The overall stroke rates for patients receiving medical therapy only, IABP only, Impella only, and ECMO were 3.39%, 3.56%, 4.54%, and 13.14%, respectively. Specifically, ischemic stroke rates were 2.93%, 3.17%, 3.96%, and 9.91%, and hemorrhagic stroke rates were 0.69%, 0.59%, 0.87%, and 4.77% for the respective groups. In stepwise forward Cox regression analysis, ECMO use was associated with the highest adjusted odds ratio (aOR) for overall stroke (aOR 3.04, 95% CI [2.66–3.48]), followed by Impella alone (aOR 1.79, 95% CI [1.61–2.00]) and atrial fibrillation (aOR 1.34, 95% CI [1.31–1.38]). However, IABP use showed no significant association with increased stroke risk in either univariate or multivariate analyses. While IABP use is not associated with an increased risk of ischemic or hemorrhagic stroke, ECMO and Impella use are linked to a higher stroke risk, particularly for ECMO-treated AMI.